A validated stability-indicating liquid chromatographic method for determination of process related impurities and degradation behavior of Irbesartan in solid oral dosage - Nishant Goswami (Wolters Kluwer Medknow Publications, 2014)
The present work describes the development and validation of a stability-indicating RP-HPLC method for the estimation of degradation and process related impurities of Irbesartan, namely Impurity-1, Impurity-2, Impurity-3 and Impurity-4. The developed LC method was validated with respect to specificity, limit of detection and quantification, linearity, precision, accuracy and robustness. The chromatographic separation was achieved on Hypersil Octadecylsilyl (4.6 mm Χ 150 mm, 3 ΅m) column by using mobile phase containing a gradient mixture of solvent A (0.55% v/v ortho-phosphoric acid, pH adjusted to 3.2 with triethyl amine) and B (95:5 v/v mixture of acetonitrile and solvent A) at a flow rate of 1.2 mL/min. The detection was carried out at a wavelength of 220 nm. During method validation parameter such as precision, linearity, accuracy, specificity, limit of detection and quantification were evaluated, which remained within acceptable limits. HPLC analytical method is linear, accurate, precise, robust and specific, being able to separate the main drug from its degradation products. The degradation products were well-resolved from the main peak and its impurities, thus proving the stability-indicating power of the method. The method is stability-indicating in nature and can be used for routine analysis of production samples and to check the stability of the Irbesartan HCl tablets.